Canções para canto e piano de José Henrique Lins: subsídios para performance - Cunha, Cláudia Roberta de Oliveira (2021)
The present work deals with the songs for voice and piano composed by José Henrique Lins Cabral de Mello (1963-2000), with an approach that aims to provide insights for the performance through literary and musical analysis of the songs. This work also presents a biographical trajectory of the composer, an edition of the handwritten scores and a catalogue of the songs, with the objective of making the composer José Henrique Lins and his work better known, besides contributing to the expansion of the repertoire of the Brazilian chamber song.